Rancang Bangun Aplikasi Pengaduan Layanan Publik Sebagai Media Pengaduan Masyarakat Desa Pagarawan Berbasis Android - Rafi Alzibar; Ahmat Josi; Vivin Mahat Putri (Jurnal Teknologi, 2026)
Public services that are still carried out manually in Pagarawan Village require people to come directly to the village office to submit complaints, which is considered inefficient in today's digital era. To address this issue, this study aims to design and develop an Android-based public service complaint application as a medium for the community to convey their aspirations digitally. The method used is the Prototype method, which includes the stages of requirements gathering, design, prototype evaluation, coding, testing, and system evaluation. System testing was carried out using Black Box testing involving the Pagarawan Village Office and the community as users. The test results showed that all main features, such as registration, login, complaints, report status monitoring, and data management by the admin, functioned properly and as needed. In addition, user satisfaction testing through User Acceptance Testing (UAT) resulted in a score of 84.32%, which falls into the “Very Good” category, indicating that the system is well-received by users and provides a satisfying user experience. This application is expected to become an effective digital innovation in improving the efficiency of complaint handling, accelerating follow-up on reports, and strengthening the quality of public services at the village level through the use of information technology.